(untitled) (Annals of Medical Research, 2022)
Aim: Percutaneus coronary intervention (PCI) is recommended as the first choice in saphenous vein graft (SVG) occlusions because of the high mortality linked with repeated coronary artery by-pass grafting (CABG). We observed percutaneous interventions performed in patients presenting with acute myocardial infarction (AMI) with a CABG history in terms of both short- and long-term efficacy and safety. Materials and Methods: The study was conducted retrospectively at a single centre. In total, 95 patients with a CABG history who were admitted to our hospital with an AMI and received PCI were included in the study. Results: In-hospital deaths occurred in 4 (4.2%) patients, 30-day major adverse cardiac event (MACE) were present in 8 (8.4%) patients, and 6 (6.3%) patients experienced first-year target vessel revascularisation (TVR). A significant difference was not observed in in-hospital death, 30-days MACE, 1-year TVR and 1-year MACE rates among the patient groups who had PCI in the graft vessel or native vessel. Conclusion: Our study revealed that a significant difference was not present in terms of MACE in the intervention of SVGs or native coronary arteries. Diabetes mellitus (DM) should be kept in mind as a predictive factor.